PENGARUH KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR KESYAHBANDARAN UTAMA BELAWAN - Ismail Fahmi (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of problem in this research there is influence of leadership on performace. There is influence of motivation on performance. There is influence organization culture on performance. There is influence leadership, motivation and organization cultue on performance. The purpose of this research is for know influence and analize of leadership on performace. For know influence and analize influence of motivation on performance. For know influence and analize influence of organization culture on performance. For know influence and analize influence of leadership, motivation and organization cultue on performance. The sample in this research is 60 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result is leadership variable influence positive and significant on performance. Motivation variable influence positive and significant on performance. Organization culture variable influence positive and significant on performance. Leadership, motivation and organization culture variable influence positive and significant on performance